Heterogeneous Fenton-like degradation of an azo dye reactive brilliant orange by the combination of activated carbon?FeOOH catalyst and H2O2. - Wu, Jinhua (Water Science and Technology)
The decoloration of an azo dye reactive brilliant orange (X-GN) by a heterogeneous Fenton system using activated carbon?FeOOH catalyst (AC?FeOOH) and H2O2 was studied. Under typical conditions (pH 7.0, H2O2 10 mmol/L, AC?FeOOH 1.0 g/L and 30 °C), 98% decoloration rate of X-GN was achieved in 240 min. The decoloration efficiency of X-GN increased with higher H2O2 dosage, higher AC?FeOOH dosage and higher reaction temperature. Though the catalytic reaction was an acid driven process, a sufficient decoloration performance was still obtained in neutral and alkaline conditions. Kinetic studies suggested that the decoloration of X-GN followed a pseudo-first order reaction and the activation energy was 17.2 kJ/mol. Iron leaching from AC?FeOOH occurred during the reaction, but the decoloration efficiency of X-GN was still higher than 80% after four runs. The AC?FeOOH has a good stability and can be reused. Besides, the generation of massive iron-containing sludge can be avoided after reaction as the remaining ferric ions in the solution were less than 1 mg/L in this combined H2O2 and AC?FeOOH process.